Digital Competence in Primary Education and the Limits of 1:1 Computing - Fraga-Varela, Fernando; Alonso-Ferreiro, Almudena (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2022)
Almost a decade after the massive incorporation of technology into schools in Galicia, Spain based on 1:1 computing programs, where teachers and students have access to laptop computers, this study explored the effects of technology on the lives of children in situations of socio-cultural and economic exclusion. Three case studies were selected from two research projects. Each case study representing three individuals. These studies were analyzed through an ethnographic approach using in-depth interviews and participant observation. The constant comparative method was used, supported by ATLAS.ti 7 qualitative analysis software. The 1:1 policies excluded the family context and the development of digital competence was heavily dependent on the opportunities provided at school. The results indicated that these policies did not reduce inequality because advanced learning experiences with information and communication technology were not provided at school.